Lifestyle tracker mobile application - Chua, Qing Wen (2022)
In recent years, obesity and overweight have become the common issues among Malaysians, especially the university students and working adults. This is due to the sedentary lifestyle and unhealthy dietary habits ad opted by the people. The situation is worsen during the COVID19 pandemic as people are required to work and stay at home. The stress problem has also arisen during the pandemic, disrupting the mental health of people. Hence, this Android mobile applicatio n development project was implemented to help people to keep track of their lifestyle. The features and functionalities of the implemented system include adding, viewing, updating and deleting the meal and exercise records, uploading food photo for meal re cord, browse and save the desired recipes and articles, share the desired articles and update the personal profile information to recalculate the daily net calories and macronutrients limit. This project solution was implemented by using React Native frame work and connected to the Flask REST API to retrieve and send the necessary information to the PostgreSQL database. The Flask REST API was deployed on Heroku to provide access for the implemented system through Internet. The selected development methodolog y for this project was incremental model, which iterated the design, development and testing phases module by module. Usability testing and user acceptance testing were carried out to assess the usability and user satisfaction with the implemented system. The overall SUS score gained by the implemented system was 94.5, which was higher than the SUS benchmark score set during the planning phase ( 75 out of 100). Hence, it could be concluded that the implemented system consists of a simple and attractive UI de sign and could function as intended. Although there are many improvements that can be made on the implemented system, t his project is still regarded as a success because it met the project's objectives and scope.